2022
DOI: 10.21608/ejchem.2022.142387.6224
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Electrochemical Investigation of a Novel Liquid Crystal as an Anticorrosion Agent for Mild Steel in Acidic Media

Abstract: In this work, inhibitory behaviour of the new azomethan compound (I-N-C8) was studied by electrochemical potentiodynamic polarization (PDP), impedance spectroscopy (EIS), and electrochemical frequency modulation (EFM), mass loss measurement, and UV-Visible spectroscopy. The structure was determined by Fourier transform infrared spectroscopy FTIR and mass spectrometry. Also the thermotropic behaviour of the studied liquid-crystal was determined by differential scanning calorimetry (DSC). The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Thermostat-controlled experiments were conducted at constant temperatures of 298, 303, 313, and 323 K in freshly produced solutions. The corrosion rate (CR) was calculated using the weight loss 39 .…”
Section: Methodsmentioning
confidence: 99%
“…Thermostat-controlled experiments were conducted at constant temperatures of 298, 303, 313, and 323 K in freshly produced solutions. The corrosion rate (CR) was calculated using the weight loss 39 .…”
Section: Methodsmentioning
confidence: 99%
“…After being cleaned with acetone, rinsed with distilled water, polished with aluminium oxide sheets of varying grades (300–2000), and given a brief opportunity to dry before being submerged in the test solution, the working electrode was put through a series of steps. PP measurements were carried out in accordance with standard working practices utilizing a Gamry Potentiostat Reference 3000-Model number and corrosion software 9 , 31 , 32 .…”
Section: Methodsmentioning
confidence: 99%
“…Organic corrosion inhibitors are one of the finest choices because of their relatively low price, high corrosion inhibition efficiency, and environmentally friendly behaviour 6 . In general, literatures reported that heterocyclic compounds with conjugated double bonds and polar groups, such as sulphur, nitrogen, oxygen are effective inhibitors of iron corrosion 7 9 . These substances work by binding the metal surface via chemisorption, physisorption, complexation, or precipitation to block oxygen from reaching the cathode, block hydrogen from diffusing from the cathode, or block metal dissolution (anodic inhibitors) 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Thermostat-controlled experiments were conducted at constant temperatures of 298, 303, 313, and 323 K in freshly produced solutions. The corrosion rate was calculated using the weight loss [39].…”
Section: Gravimetric Techniquementioning
confidence: 99%